Breakouts—A Radiological Sign of Poor Prognosis in Patients With Brain Metastases - Blazquez, Raquel; Proescholdt, Martin Andreas; Klauser, Marlene; Schebesch, Karl-Michael; Doenitz, Christian; Heudobler, Daniel; Stange, Lena; Riemenschneider, Markus J.; Bumes, Elisabeth; Rosengarth, Katharina; Schicho, Andreas; Schmidt, Nils-Ole; et al. (Frontiers in Oncology, 2022)
Purpose: Brain metastases (BM) can present a displacing or infiltrating growth pattern, independent of the primary tumor type. Previous studies have shown that tumor cell infiltration at the macro-metastasis/brain parenchyma interface (MMPI) is correlated with poor outcome. Therefore, a pre-therapeutic, non-invasive detection tool for potential metastatic cell infiltration at the MMPI would be desirable to help identify patients who may benefit from a more aggressive local treatment strategy. The aim of this study was to identify specific magnetic resonance imaging (MRI) patterns at the MMPI in patients with BM and to correlate these patterns with patient outcome. Patients and methods: In this retrospective analysis of a prospective BM registry, we categorized preoperative MR images of 261 patients with BM according to a pre-specified analysis system, which consisted of four MRI contrast enhancement (CE) patterns: two with regularly shaped borders (termed “rim-enhancing” and “spherical”) and two with irregular delineation (termed “breakout” and “diffuse”). The primary outcome parameter was overall survival (OS). Additionally analyzed prognostic parameters were the Karnofsky Performance Index (KPI), tumor size, edema formation, extent of resection, and RPA class. Results: OS of patients with a breakout pattern was significantly worse than OS of all other groups. Conclusion: Our data show that BM with a breakout pattern have a highly aggressive clinical course. Patients with such a pattern potentially require a more aggressive local and systemic treatment strategy.